Creating Partnerships for Improving Oral Health of - Candace M. Jones, MPH; Norman Tinanoff, DDS, MS; Burton L. Edelstein, DDS, MPH; (Blackwell Synergy, 2000)
Dental caries in primary teeth of children 5 years of age or younger is still one of the major health problems in the United States, especially for lowincome children (1). This largely preventable disease continues to affect many children in lower socioeconomic strata and many ethnic minorities.